Digital Rock Physics Investigation in Outcrop Sandstone Reservoir - . Handoyo; . Fatkhan; F. D.E. Latief; R. Rizki; H. Y. Hutami (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Porosity and permeability of the reservoir rocks can be calculated using digital rock physics. This technique is one of the fastest and effective ways to calculate the value of porosity and permeability based on rock sample images. The samples observed in this paper were gathered from the outcrop of oil-filled sandstone formation. The technology of digital rock physics allowed us to predict the physical properties, mainly porosity and permeability, in the outcrop sandstone samples. The digital image model displayed in the 2D and 3D images and the complexity of pore geometry as well. From the image, we develop the digital simulation to predict the value of porosity and permeability in the 3D samples. By applying this method, we have confirmed that the target area of this research is potential to be a reservoir, which is porous and clean.